Death and the family: testing Andean lineage tombs through cranial non-metrics - Herrera, Sarah Frances, author; Magennis, Ann, advisor; Van Buren, Mary, advisor; Lacy, Michael, committee member (Colorado State University. Libraries, 2016)
Historical records indicate that ancestor worship was practiced as part of ayllu social organization in the Inka empire during the Late Horizon and beginning of the Colonial Period (1440 A.D. - 1650 A.D.). This same set of beliefs and practices is often ascribed to the Late Intermediate Period (900 A.D. – 1440 A.D.) throughout the Andes by many researchers (Doyle 1988; Herrera 2003; Ibarra 2013; Isbell 1997; Mantha 2006; Martiarena 2014). It is important for the study of any site so far removed from the historical records to be cautious when using these documents for the interpretation of the archaeological record. The significance of this study is that little has been done using a bioarchaeological approach to test the assumptions of ayllus and ancestor worship based on historical records in the Conchucos region far removed from the center of the Inka empire. The site of Marcajirca is located on the ridge of a sacred ancestor mountain, Mt Llamoq, in North Central Peru. Although the site is a village, it has an especially large amount of mortuary architecture consisting of above ground tombs or chullpas, as well as caves, and underground structures that contain human remains. One way to infer ayllu organization and ancestor worship as well as validate the use of historical records for Marcajirca would be to identify affinity and kinship structure through family burials in combination with material evidence that these burials were used for ancestor worship. Were the chullpas and caves at the Late Intermediate Site of Marcajirca reserved for family burials and ancestor worship? In order to test this, I attempted to determine if the people in one tomb were significantly different biologically from the people found in other tombs based on the relative prevalence of heritable non-metric traits. Twenty four non-metric traits on 106 crania from 15 different tombs were scored. The frequencies of these non-metric traits were used to calculate the mean measure of divergence to produce a numerical summary of the biological distance between groups of skeletal remains. There were a few noticeable patterns from the non-metric analyses at Marcajirca. Cave 19 differs the most from other tombs at statistically significant levels. Many of the other caves and chullpas do not exhibit statistically significant differences and often exhibit negative distance values. These results do not provide enough information to positively identify each tomb as a unique family burial, but may be more indicative of a wider ayllu group present at Marcajirca. Only Cave 19 represents a distinct group, possibly from an outlying community that considered itself as part of the larger ayllu linked by their belief in Llamoq as its founding ancestor. In the case of Marcajirca, it does appear as though many of these records can be accurately applied to the archaeological interpretations for this site and its role in the regional ayllus. Future research based on intersite biodistance analysis could be used to determine if there was a real biological distinction between the various ayllus reported to exist in the Conchucos Region.
Keywords: ayllu; tombs; archaeology; ancestor worship; biodistance; Andes